Involvement of Non-governmental Organizations in Promoting Primary Education in Bangladesh - Alam, Md. Azizul (Westscience Press, 2025)
The aim of this article is to investigate the engagement of non-governmental organizations (NGOs) in primary education activities in Bangladesh as development agents. We understand that non-governmental organizations (NGOs) have immense potential as catalysts of social change, and we analyze numerous aspects that affect their purported powers. Investing in developing NGOs and service delivery capacities is crucial for their long-term viability as intermediaries in meeting societal demands. The number of NGOs has soared in Bangladesh during the past decade largely because foreign donors have made funds available to them. Over the past decade, donors have increasingly turned their attention to NGOs to provide funds to community-based programs. The principal task of most NGOs in Bangladesh has been to undertake various poverty alleviation and empowerment of women programs in rural areas. Many NGOs have placed education and health as a top priority, as they play a crucial role in human resources development. Therefore, in this paper, it is propitious for non-governmental organizations to make solid contributions to strengthening the institutional fabric of primary education in Bangladesh.